The Struggle for Independence in Guinea-Bissau - Carlos Eduardo Sangreman; Rui Jorge Semedo (Journal of Contemporary Sociological Issues, 2022)
The realization of the process of armed struggle for national liberation in the so called Portuguese Guinea and, consequent unilateral proclamation of the State of Guinea-Bissau in September 1973 was possible from outside the Guinean borders, through an important and strategic contribution made by the Republic of Guinea- Conakry which in 1958 had already achieved national independence. This article intends to observe the capital of the neighboring Republic of Guinea as a symbolic structuring space in the construction of ideological antagonisms based on the sociocultural and political dispute around "unity and against unity" within the African Party for Independence of Guinea and Cape Verde (PAIGC). The fundamental purpose is to understand the extent to which the environment generated in Conakry contributed to the cohesion or weakening of the recommended desiderates, but above all to the legacy of inherited conflicts that influenced the post-independence state building process in Guinea-Bissau. It is worth mentioning that the empirical framework is the PAIGC, the sociopolitical segments that make up its internal structure and other protagonists of the process. Keywords: Conakry, PAIGC, Unity and Conflicts, Guinea-Bissau.